Food web organization following the invasion of habitat-modifying Tubastraea spp. corals appears to favour the invasive borer bivalve Leiosolenus aristatus. (February 2018) - Vinagre, Catarina; Silva, Rodrigo; Mendonça, Vanessa; Flores, Augusto A.V.; Baeta, Alexandra; Marques, João Carlos
Graphical abstract: Highlights: Isotopic analysis was conducted in areas invaded by Tubastraea spp. Eleven food web nodes were isotopically characterized. Food web was dominated by suspension feeders. Invasive borer bivalve Leiosolenus aristatus is a suspension feeder. L. aristatus invasion is likely facilitated by the Tubastraea spp. invasion. Abstract: The rapid expansion of the invasive coral, Tubastraea spp., along the coast of Brazil is considered a serious problem with major ecological and socio-economic impacts. However, studies on the structure and dynamics of the food web associated to this coral, are still missing. At the basis of this coral another non-indigenous species is very often found, the mytilid Leiosolenus aristatus, a borer bivalve that perforates the calcareous base of Tubastraea spp. and seems to be profiting from the invasive nature of its coral host. Stable isotopic analysis was applied to the main macro-organisms occurring amidst Tubastraea spp. colonies, to 1) provide the first trophic characterization of the food web associated with Tubastraea spp., and to 2) elucidate if L. aristatus has a trophic link to its coral host Tubastraea spp. The food web that accompanies this invasive coral seems to be mostly composed of suspension feeders. It was also concluded that both Tubastraea spp. and L. aristatus are both suspension feeders consuming similar resources. This way, L. aristatus seems to profit from the expansion of Tubastraea spp. because the coral provides valuable habitat where food resources are likely abundant. The coral, however, does not directly nourish the boring bivalve. As Tubastraea spp. progresses in its invasion of new areas, L. aristatus should follow. Such interaction appears to constitute an illustration of the invasion meltdown hypothesis, which states that the negative impacts of non-indigenous species will be intensified by their interactions with other invasive species.